Implementation of Government Regulation No. 2/2003 and Perkap No. 14/2011 on Code Enforcement in Polres Purworejo - Purwanto Purwanto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
The purpose of this study was to determine the effectiveness of the law in PP 2/2003 of Police Regulation No.14 of 2011 of Police Purworejo. In accordance with the existing problems, then it can be taken a result that the implementation of the Police Regulation in police office of Senapelan not run well, because there is no doing dissemination to all members of the police office of Senapelan. In practice there is still a member of the Police office of Senapelan who committed the violation of disciplinary violations and the duty defaulters Police Regulation No.14 of 2011 on the prohibition of the institutional ethics Article 13 paragraph 1 have mentioned that every member of the Police banned avoid or reject the official orders and paragraph 4 fellow member KEPP prohibited from KEPP breach of agreement or disciplinary or criminal offenses. In the implementation of sanctions against members of the police in the police office of Senapelan committing criminal offenses only did the Code without prior Assembly Session at the General Court. Whereas in Article 22 paragraph states the following sanctions decided by the trial PDTH recommendations KEPP after the first proven criminal offense through the judicial process general to a court decision which has permanent legal force.Keywords: Law Enforcement, Code of Ethics.